Fetal nuchal fold thickness measurement between 18 and 24 weeks of pregnancy: reference intervals for a Brazilian population. (January 2015) - Araujo Júnior, Edward; Martins, Wellington P.; Pires, Claudio Rodrigues; Santana, Eduardo Félix Martins; Zanforlin Filho, Sebastião
Abstract Objective: To determine reference intervals of fetal nuchal fold (NF) thickness measurement in the second trimester of pregnancy in a Brazilian population. Methods: This was a retrospective cross-sectional study with 2559 normal singleton pregnancies between 18 and 24 weeks of pregnancy. The fetal NF was obtained in the axial plane of fetal head at level of lateral ventricles including the cavum septum pellucidum, third ventricle, thalamus and transverse cerebellar diameter. The NF was measured posterior to the occipital bone, from the bone surface to the skin, including only soft tissue. To assess the correlation between fetal NF and gestational age (GA), polynomial equations were calculated and adjusted to determination coefficient (R2). Results: The mean fetal NF ranged from 3.98 ± 1.14 mm at 18 − 18 + 6 to 4.83 ± 0.93 mm at 24 − 24 + 6 weeks of gestation. A good correlation was observed between fetal NF and GA, which is better represented by a linear equation: NF = 1.055 + 0.158*GA (R2 = 0.06). Conclusion: Reference intervals of fetal NF thickness measurement in the second trimester of pregnancy were determined for a Brazilian population.